Virtuous effects of religion on negative emotions among offenders in a Colombian prison - Jang, Sung Joon (Journal of crime and justice, 2024)
Although prior research documents a positive relationship between religious involvement and emotional well-being among incarcerated individuals, the salutary effect of religion on mental health remains in need of scientific scrutiny. To examine this understudied issue, we hypothesized that prisoner religiosity is positively associated with virtues, which are in turn inversely related to negative emotions. To test this hypothesis, we applied structural equation modeling to analyze data from a survey with a convenience sample of 139 males housed at a Colombian prison. As hypothesized, we found that both public (religious service attendance) and private religious behaviors (praying and reading a sacred book) were positively associated with the virtues of forgiveness, self-control, and gratitude. Additionally, we found that forgiveness and self-control were inversely related to state anger, depression, and anxiety. Finally, self-control was central in explaining the relationship between religious service attendance and state anger. Implications and limitations of the present findings are discussed.